Concentration dependent supramolecular interconversions of triptycene-based cubic, prismatic, and tetrahedral structures. Issue 40 (24th January 2018) - Chakraborty, Sourav; Endres, Kevin J.; Bera, Ranajit; Wojtas, Lukasz; Moorefield, Charles N.; Saunders, Mary Jane; Das, Neeladri; Wesdemiotis, Chrys; Newkome, George R.
Abstract : New insight into the molecular fission–fusion process is obtained with the characterization of a stable intermediate prismatic cage. Abstract : The quantitative, single step, self-assembly of a shape-persistent, three-dimensional C 3 v -symmetric, triptycene-based tris-terpyridinyl ligand initially gives a platonic-based cubic architecture, which was unequivocally characterized by 1D and 2D NMR spectroscopy, mass spectrometry, and single crystal X-ray structural analysis. The unique metal–ligand binding properties of the Cd 2+ analogue of this construct give rise to a concentration-dependent dynamic equilibrium between cube, prism, and tetrahedron-shaped architectures. Dilution transforms this cube into two identical tetrahedra through a stable prism-shaped intermediate; increasing the concentration reverses the process.